A Modified Taylor Series Expansion Method for Solving Fredholm Integro-Differential Equations (Global Journal of Science Frontier Research, 2021)
In this paper, we use a modified Taylor series expansion method for solving the linear Fredholm integro-differential equations. This method transfroms the equation to linear system equations that can be solved easily with reduced row echelon method. Finally, we show the efficiency of this method with numerical examples by comparing the approximate solutions with exact solutions.
Keywords: fredholm integro-differential equations; numerical method; taylor; series